TEACHING LISTENING COMPREHENSION: SOME IMPORTANT ASPECTS FOR MATERIAL DEVELOPMENT AND TEACHING TECHNIQUES - Patrisius Djiwandono (Indonesian JELT, 2015)
The paper discusses aspects of spoken language that should beconsidered in the development of teaching materials, andproposes a few techniques for teaching listeningcomprehension. It starts with an overview of importantcharacteristics of spoken discourse, which include phonology,accents, prosodic features, speech rate, and discoursestructure. It then argues that spoken input varies according totwo major distinctions, namely CALP (Cognitive AcademicLanguage Proficiency) and BICS (Basic InterpersonalCommunication Skills) and that efforts should be directed tothe former if the materials are intended for academic purposes.It maintains that the materials should incorporate aspects ofstrategies for listening that help learners overcomecomprehension barriers and gain the most from the spokeninput. Some principal considerations in grading listeningmaterials are presented according to five parameters, whichinclude linguistic characteristics, explicitness, organization,content and context. Finally, the paper proposes a fewteaching techniques that promote strategic listeningcomprehension for EFL learners of intermediate up to preadvancedlevel in an academic setting.Keywords: teaching, listening, strategies, materialdevelopment